Genome-wide CRISPR screens and their applications in infectious disease - Srivastava, Kaveri; Pandit, Bhaswati (Frontiers in Genome Editing, 2023)
Inactivation or targeted disruption of a gene provides clues to assess the function of the gene in many cellular processes. Knockdown or knocking out a gene has been widely used for this purpose. However, recently CRISPR mediated genome editing has taken over the knockout/ knockdown system with more precision. CRISPR technique has enabled us to perform targeted mutagenesis or genome editing to address questions in fundamental biology to biomedical research. Its application is wide in understanding the role of genes in the disease process, and response to therapy in cancer, metabolic disorders, or infectious disease. In this article, we have focused on infectious disease and how genome-wide CRISPR screens have enabled us to identify host factors involved in the process of infection. Understanding the biology of the host-pathogen interaction is of immense importance in planning host-directed therapy to improve better management of the disease. Genome-wide CRISPR screens provide strong mechanistic ways to identify the host dependency factors involved in various infections. We presented insights into genome-wide CRISPR screens conducted in the context of infectious diseases both viral and bacterial that led to better understanding of host-pathogen interactions and immune networks. We have discussed the advancement of knowledge pertaining to influenza virus, different hepatitis viruses, HIV, most recent SARS CoV2 and few more. Among bacterial diseases, we have focused on infection with life threatening Mycobacteria, Salmonella, S. aureus, etc. It appears that the CRISPR technique can be applied universally to multiple infectious disease models to unravel the role of known or novel host factors.